A trajetória do autismo na educação: da criação das associações à regulamentação da política de proteção (1983-2014) - Castanha, Juliane Gorete Zanco (2016)
Brazil created the “Nacional Politics of Protection of People’s Rights with Disorders of Autism Spectrum”, through the Implementation of decree n. 12.764/2012, two years later, through the Implementation of decree n° 8.368/2014, it legalized referred Politics, which received a significant support with the promulgation of Law n. 13.146/2015, known as the “Brazilian Law of Inclusion” or “Statute of Person with Disability”. They were/are much expressive legal achievements, that intensify and stimulate the process of educational and social inclusion of people with autism. About this legal achievements we can question: Do they result of impositions of international organisations to Brazilian State? Does it express the actions of a benevolent and solidary State? Or are they results of long and intensive struggle of autistics’ parents and friends associations, of professional and researchers that required the intervention of State? Does the fact that we have achieved advances in the legislation ensures life and education’s quality for autistcs? In front of exposed, it constituted as the central objective of the present study to understand the way of autism in Brazilian education between 1983 and 2015, in other words, to rescue historically, the process of autistics’s inclusion, seeking to articulate dialectically movements of parents and parents and friends’ associations of autistics, to the guarantees of rights and politics of inclusion created by State. As specific objectives we intend: a) To situate the autistics’ education in a context of special education modality; b) To understand the role of parents and parents and friends’s associations ensuring for the autistics’ rights. In order to achieve these objectives, the study adopt as analysis methodology the dialectics focusing contradictions between demands of movements around of autistics’ rights and actions/reactions of several sectors resulted of State. The research had as sources for analysis the legislation, articles of written press, as the Folha de São Paulo, Veja newspaper, Jornal de Beltrão, bibliographies of memorialistic character, several bibliographies and interviews with autistics’s parents that are in front of institutions or are researchers about the issue. At first moment, the text problematizes the contradictions between inclusion/exclusion and emancipation in the capitalist society, stage, which we are insirted; Subsequently it reconstructs the process of insertion of mentally impaired, specially the autistics, in educational system; Later, it recovers the history about two institutions founded by parents that dedicate to autistics, as AMA-SP and the APADV, in Dois Vizinhos in Paraná; finally it shows some experiences of inclusion of autistics and the discussions about this inclusion, in other words, it reflects about the challenges for the inclusion of autistics in regular or common education. We can see that there are a hegemony on the school inclusion of people with disability idea, but, in practice, the inclusion still is approaching more of exclusion, segregation. First steps have been taken, but, the struggle for real, full inclusion, that lead to emancipation of people with desabilities, amoung them autistics, still require a lot of our energies to discuss, study, question, collect